Malaysia Economic Monitor, December 2013 : High-Performing Education - Gil Sander, Frederico (World Bank, Bangkok, 2014)
Malaysia's economy regained momentum but yearly growth is set to decelerate in 2013. Export recovery into 2014 is expected to offset slower domestic demand and lead to a pick-up in growth. Fiscal consolidation is picking up pace with subsidy cuts, sin tax increases, and less generous public service bonuses. The full implementation of the minimum wage in January 2014 will provide an additional boost to households, as will increased cash transfers that are part of the government's strategy for subsidy rationalization and modernizing social protection. Malaysia performs very well with respect to access to education. Enrolments at primary and lower secondary levels are nearly universal and recent gains in pre-primary education have been note-worthy. Among East Asian countries that participated in the 2012 Program for International Student Assessment (PISA), Malaysian students only outperform their Indonesian peers, and lag even lower-income countries (including, by a wide margin, Vietnam). Expenditure on basic education is more than double that of other Association of Southeast Asian Nations (ASEAN) countries and the decline in learning outcomes occurred while inputs to education were expanding and the size of the student population was falling. The key constraints to improving the quality of basic education thus relate not to the quantity of inputs but institutions. 46 percent of principals report a lack of qualified teaching staff as a constraint, and Ministry of Education (MOE) admits that in recent years some candidates enrolling in teacher training institutions did not meet minimum requirements of academic achievement at the secondary level. Lifting these constraints entails refining some of the measures recommended in the Education Blueprint for high-performing education system: (1) moving towards school-based decision-making; (2) improving parental involvement and enhancing accountability; and (3) improving incentives and recruitment for teachers. The government may consider piloting fixed contract recruitments with tenure contingent on performance, and tying retraining and up-skilling efforts with certification.